Contents of arsenic and some other elements in stream sediments and waters of the Medija drainage basin, central Slovenia - Teršič, Tamara; Miler, Miloš; Gaberšek, Martin; Gosar, Mateja (Geologija, 2018)
In Znojile, north of the Kotredež village, a small antimonite mine was operating in the first half of the 20th century. After flooding in 1994 and 2010, when part of the material from the mine waste deposit was washed away, a number of investigations on soil and plants contamination in the area of Zagorje ob Savi municipality were carried on. It was established that the area of Kotredeščica valley, between Rove and Znojile settlements, is enriched with arsenic. In 2017 river sediments and water at 13 locations in Kotredeščica and Medija valleys were sampled in order to establish the sources of increased arsenic and antimony contents. 7 samples were taken from Kotredeščica, 2 samples from Orehovica and 4 samples from Medija. The determined median for As in sediment samples is 29.5 mg/kg. As contents are the highest in the upper course of Kotredeščica and decrease downstream. The established median for Sb in sediment samples is 6.4 mg/kg. The highest contents were determined in the sediments in the upper course of Kotredeščica and in Orehovica. In water samples the determined medians for As and Sb are 0.85 µg/l and 2.39 µg/l respectively, the highest concentrations were measured in Kotredeščica. With SEM/EDS analysis of sediments it was established that As is mostly present in the form of iron oxyhydroxy sulphates with smaller amounts of As and to a lesser extent in the form of mineral arsenopyrite. Sb is bound to somewhat porous mineral grains of antimonite. We assume that increased As and Sb contents in sediments and waters are the consequence of washing out and dissolution of the material from mine waste deposits as well as the increased natural background for As and Sb in this area, which is the consequence of the natural ore occurrences.